Pengaruh Profitabilitas dan Solvabilitas terhadap Keputusan Lindung Nilai - Agma Aureole First Stecyia Payung; Dewa Putra Khrisna Mahardika (Syntax Literate, 2023)
Energy is one of the sectors that affect a country's economy. The ever-increasing level of energy consumption affects the productive power of the energy sector. Hedging is a way used to hedge assets owned by the company from losses incurred due to risk. The object of this study is oil, gas and coal sub-sector companies listed on the IDX. The period in this study is 2019-2021. In this study, hedging decisions are proxied with dummy variables, where companies that do hedging will be given a score of 1 and companies that do not hedge will be given a score of 0. While profitability is proxied by the Return on Assets formula and solvency is proxied by the Debt-to-Equity Ratio formula. The total population in this study is 59 companies. The technique of logistic regression was utilized as the approach to analysis for this particular research project. The finding in the results of this study is that profitability using return on assets indicators does not affect the company's decision to do hedging. Solvency using the debt-to-equity ratio indicator does not affect the company's decision to hedge. It is anticipated that the findings of this study would expand people's awareness on hedging and are expected to be considered by companies to make hedging decisions.